2009
DOI: 10.1007/s12663-009-0065-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two point rigid internal fixation in the management of zygomatic complex fracture

Abstract: Purpose To evaluate the efficacy of two point rigid internal fixation in the immobilization of zygomatic complex fractures. Patients and methods 30 patients with zygomatic complex fractures were managed by open reduction and internal fixation using titanium mini bone plate screws at the frontozygomatic and zygomatic buttress region. This prospective study was carried out at the Department of Oral & Maxillofacial Surgery, Armed Forces Medical College (AFMC), Pune, India between 1st August 2005 to 1st August 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 19 publications
1
31
0
2
Order By: Relevance
“…In our study population, the male/female participants proportion was 3.1:1; in Chakranarayan et al, 9 Salonen et al 10 have…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…In our study population, the male/female participants proportion was 3.1:1; in Chakranarayan et al, 9 Salonen et al 10 have…”
Section: Discussionmentioning
confidence: 46%
“…[4][5][6][7] Some authors have reported that right-side injuries were common than the left side. [8][9][10] A retrospective study was conducted in our center about the pattern and etiology of the maxillofacial injuries. The percentage of the right-side injuries was higher than the left side, and was statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…Among prominent bones of the facial skeleton, zygomatic bone occupies the most notable position and it not only act as major buttress of the mid face, but also plays important role in facial width determination. 15,16 Considering this important part of the facial skeleton, a more proactive approach had been adopted for the reduction methods of zygomatic complex fractures during the last two decades. 17 Our study was aimed to evaluate the efficacy of the two treatments i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Chakranarayan et al 4 realizaram um estudo avaliando a eficácia de fixação das fraturas zigomáticos em 02 pontos, e concluíram que a fixação da região frontozigomática e do pilar zigomaticomaxilar são satisfatórias como método de fixação para as fraturas do osso zigomático.…”
Section: Discussionunclassified
“…A análise epidemiológica destas fraturas é dependente da condição socioeconômica, cultural, e geográfica do local de estudo, sendo que a maior parte dos trabalhos encontram um predomínio de pacientes do gênero masculino, de 21 -40 anos de idade 2,3 . Quando o CZM sofre um trauma de alta energia, a moldura orbital e as paredes internas da órbita podem sofrer fraturas com alta complexidade, apresentado deslocamentos e cominuição que dificultam o tratamento cirúrgico 4 . A abordagem destas fraturas é baseada no acesso direto a todos os pontos fraturados via acessos cirúrgicos amplos, redução óssea com reestabelecimento das dimensões da face, fixação de no mínimo 03 pontos com placas e parafusos dos sistemas 1.5 e 2.0mm, seguido de reconstrução das paredes internas orbitárias utilizando-se enxertos autógeno, malhas de titânio ou biomateriais 5,6 .…”
Section: Introductionunclassified